Choosing the right partner in hormone-dependent gene regulation: Glucocorticoid and progesterone receptors crosstalk in breast cancer cells - Pecci, Adali; Ogara, María Florencia; Sanz, Rosario T.; Vicent, Guillermo Pablo (Frontiers in Endocrinology, 2022)
Steroid hormone receptors (SHRs) belong to a family of ligand-activated nuclear receptors that share certain characteristics and possess others that make them unique. It was thought for many years that the specificity of hormone response lay in the ligand. Although this may be true for pure agonists, the natural ligands present a broader effect by simultaneous activation of several SHRs. Moreover, SHRs share structural and functional characteristics that range from similarities between ligand-binding pockets to recognition of specific DNA sequences. These properties are clearly evident in progesterone (PR) and glucocorticoid receptors (GR); however, the biological responses triggered by each receptor in the presence of its ligand are different, and in some cases, even opposite. Thus, what confers the specificity of response to a given receptor is a long-standing topic of discussion that has not yet been unveiled. The levels of expression of each receptor, the differential interaction with coregulators, the chromatin accessibility as well as the DNA sequence of the target regions in the genome, are reliable sources of variability in hormone action that could explain the results obtained so far. Yet, to add further complexity to this scenario, it has been described that receptors can form heterocomplexes which can either compromise or potentiate the respective hormone-activated pathways with its possible impact on the pathological condition. In the present review, we summarized the state of the art of the functional cross-talk between PR and GR in breast cancer cells and we also discussed new paradigms of specificity in hormone action.